2011
DOI: 10.3390/rs3051047
|View full text |Cite
|
Sign up to set email alerts
|

Roads as Drivers of Change: Trajectories across the Tri‑National Frontier in MAP, the Southwestern Amazon

Abstract: Regional studies of land cover change are often limited by available data and in terms of comparability across regions, by the transferability of methods. This research addresses the role of roads and infrastructure improvements across a tri-national frontier region with similar climatic and biophysical conditions but very different trajectories of forest clearing. The standardization of methodologies and the extensive spatial and temporal framework of the analysis are exciting as they allow us to monitor a dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 30 publications
(26 reference statements)
3
89
0
9
Order By: Relevance
“…For example, new economic opportunities for forest-dependent people are inducing a transition from traditional extractive activities to greater investment in cattle ranching (Salisbury and Schmink 2007;Gomes 2009;Coomes et al 2016). In addition, trans-boundary road connectivity through the southwestern Amazon, although relatively recent, is already leading to forest conversion in this key Brazil nut-producing region (Southworth et al 2011;Perz et al 2013). Moreover, market fluctuations in Brazil nut prices (which remove incentives for producers to maintain production) and policy failures (such as when governments do not defend extractivist property rights or introduce regulations that undercut harvesters; e.g., Perales and Guariguata 2015), are worrisome.…”
Section: The Resource Systemmentioning
confidence: 99%
“…For example, new economic opportunities for forest-dependent people are inducing a transition from traditional extractive activities to greater investment in cattle ranching (Salisbury and Schmink 2007;Gomes 2009;Coomes et al 2016). In addition, trans-boundary road connectivity through the southwestern Amazon, although relatively recent, is already leading to forest conversion in this key Brazil nut-producing region (Southworth et al 2011;Perz et al 2013). Moreover, market fluctuations in Brazil nut prices (which remove incentives for producers to maintain production) and policy failures (such as when governments do not defend extractivist property rights or introduce regulations that undercut harvesters; e.g., Perales and Guariguata 2015), are worrisome.…”
Section: The Resource Systemmentioning
confidence: 99%
“…Even with the urban focus, other variables are likely important. Although deemed not important at the workshop, transportation networks could still be an important driver of land cover change [51]. Groundwater restriction zones, while having real consequences in rural lands, may not be a severe impediment to growth in urban land, since they are fed by surface supplies in our study area [52].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the pattern of seismic exploration did not align with the subsequent development of agricultural roads, small-holder agricultural plots and the fishbone pattern often created by colonists in tropical rainforests [18]- [20].…”
Section: Geospatial Studies Of Extractive Landscapesmentioning
confidence: 99%